Higher titres of thyroid antibodies among the urban & coastal populations of Malaysia - Shahar, Mohammad Arif; Omar, Ahmad Marzuki; Ab Wahab, Norasyikin; Sukor, Norlela; Kamaruddin, Nor Azmi (Korean Thyroid Association, 2017)
To determine the prevalence of anti-thyroperoxidase (antiTPO) and anti-thyroglobulin (antiTG) and the associated predisposing factors among the Malaysian adult population. A cross sectional study involving 2259 subjects selected from 5 pre-assigned regions which were representatives of the Malaysian socioeconomic and geographical background. Sixty-nine subjects were excluded due to incomplete data. The prevalences of antiTPO and antiTG were determined for 2054 subjects who did not report any history of thyroid diseases nor taking any thyroid medications (disease-free population). Hundred thirty-six subjects with known thyroid disorders were further analysed in terms of their thyroid antibody status. The influence of demographic factors on antiTPO and antiTG titres was also analysed. Positive antiTPO and antiTG were defined as titres above 40 IU/mL. The hormonal assays and thyroid antibodies were performed using the Architect and Immulite systems respectively. The prevalence of positive antiTPO and antiTG were 12.2% and 12.1% respectively. Among the disease-free population, the prevalence of positive antiTPO and antiTG were 10.4% and 10.9% respectively. Among subjects with known thyroid disease, the prevalence of antiTPO and antiTG were 39.0% and 30.1% respectively. Higher prevalence of antiTPO and antiTG was observed females (15.2% and 15.7% respectively). Among the major ethnic groups, Indians had a higher prevalence of antiTPO but not antiTG titres. There was also a trend of higher prevalence of thyroid antibodies in urban and coastal regions of the studies areas. Only 8% and 9% of those with positive antiTPO were hypo- and hyperthyroid respectively. Seven percent and 8% of those with positive antiTG were hypo- and hyperthyroid respectively. The prevalence of antiTPO and antiTG in this population were 12.2% and 12.1% respectively. Higher prevalence of thyroid antibodies was observed in females and Indians. The higher prevalence of thyroid antibodies in urban and coastal areas may be a reflection of iodine availability.